Pembuatan Pupuk Kompos Cair dari Air Buangan Industri Tahu - Rakhmayani, Indah; Aulia, Nabila Shafa; Noviyanti, Noviyanti; Jati, Dian Rahayu; Apriani, Isna (Jurnal Teknologi Lingkungan Lahan Basah, 2020)
Abstract Cleaner production is an environmental processing strategy that is implemented on an ongoing basis to increase eco-efficiency in order to reduce risks to human health and the environment. The tofu industry in its production process produces waste, both solid and water. Disposal of waste directly to water bodies will damage the environment by creating unpleasant odors and the hot temperature of waste water which can affect the growth of aquatic biota. Tofu production produces 150 L of liquid waste from the soaking and filtering process. Meanwhile, 50 kg of solid waste is produced from milling soybeans. Solid waste will be used as animal feed and liquid waste will be processed into liquid compost. Keywords: Tofu Production, Cleaner Production, Liquid Compos, Waste Minimization, Mass Balance. Abstrak Produksi bersih merupakan strategi pengolahan lingkingan yang diterapkan secara berkelanjutan untuk meningkatkan ekofisiensi agar dapat mengurangi resiko terhadapat kesehatan manusia dan lingkungan. Industri tahu dalam proses produksinya menghasilkan limbah, baik padat maupun air. Pembuangan limbah langsung ke badan air akan merusak lingkungan dengan timbulnya bau tidak sedap dan suhu air limbah yang panas dapat mempengaruhi pertumbuhan biota air. Produksi tahu menghasilkan limbah cair sebanyak 150 L dari proses perendaman, dan penyaringan. Sedangkan limbah padat yang dihasilkan sebanyak 50 kg yang berasal dari penggilingan kacang kedelai. Limbah padat akan dijadikan pakan ternak dan limbah cair akan diolah menjadi pupuk kompos cair. Kata Kunci : Industri Tahu, Produksi Bersih, Pupuk Kompos, Minimasi Limbah, Neraca Massa.